Printing photonic-based thermal barrier coatings onto metal alloy - Alberto Gomez-Gomez; Diego Ribas Gomes; Benedikt F. Winhard; Laura G. Maragno; Antoine E. Jimenez; Marie Thibaudet; Julia Brandt; Alexander Petrov; Manfred Eich; Kaline P. Furlan (Nature Communications)
Abstract Reflective coatings based on photonic crystals and photonic glasses are usually produced by traditional colloidal self-assembly techniques characterised by limited control over the deposition surface and lengthy processing times. The emergence of Additive Manufacturing combined with Colloidal Assembly (AMCA) has enabled fast and precise deposition of homogeneous photonic structures, whilst circumventing issues such as the undesired coffee-ring effect. However, the application of this technique was limited to flat substrates. This study investigates the AMCA of ceramic-based colloidal structures onto metallic curved surfaces, relevant to the field of thermal barrier coatings (TBCs). Our results demonstrate the homogeneous ceramic-based photonic glass coatings can be AMCA-printed on different substrates only when a conscious surface charge matching between the colloidal particles and the substrates is made. It also demonstrates the importance of controlling the contact angle of the suspension on the substrates and the printing geometry strategy, differing from traditional direct writing. We further demonstrate the versatility of this method by printing highly porous three-dimensional gadolinium zirconate structures onto curved Inconel substrates. These coatings are engineered for their use as reflective “photonic-based” thermal barrier coatings (rTBCs), capable of suppressing both radiative and conductive heat transport. The resultant AMCA-printed Gd2Zr2O7 rTBCs outperform state-of-the-art TBCs in terms of their reflectance properties and provide a reliable thermal protection to the underlying Inconel alloy, lowering its temperature by about 150 °C in a torch experiment.